Analysis of fiscal dependency of municipalities of sixth category in Boyacá, from 1996 to 2012 - Delgado Ruiz, Siervo Tulio; Acero Jiménez, Luis Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The Constitution of 1991 has made fiscal decentralization deeper as it has augmented the number of transferences from the central government towards the territorial level of the State, apart from having redefined the functions of the different governmental levels and increased the responsibilities of the local governments. Revenues that generate the greater income are still monopolized by the central government, resulting in a diminished possibility for the local governments -who are financed almost solely by transferences from the central government- to impose new tax rates. This phenomenon causes the municipalities to be highly dependent from the central government, especially those who have a nearly inexistent capacity for generating their own revenues.